Estudo sistemático de duas espécies de Acontiaria (Cnidaria, Anthozoa, Actiniaria) da Baía de Guanabara, Rio de Janeiro, Brasil - Pires, Débora de Oliveira (1987)
Two species of sea anemones (Cnidaria, Anthozoa, Actiniaria) from Guanabara Bay, Rio de Janeiro, Brazil, were studied. They are both from the subtribe Acontiaria Carlgren (in Stephenson, 1935). These anemones are Haliplanella lineata (Verrill, 1869) and a new genus, new species, both of the family Haliplanellidae Hand, 1956. Haliplanella lineata is cosmopolitan and had already been registered in Rio de Janeiro (Belém & Monteiro, 1977). The new species, up to now, has only been found in Guanabara Bay. The study of nematocysts was emphasized, highlighting their relevant contribution to the Actiniaria systematics. Weill's (1934) and Schmidt’s (1969, 1972, 1974) nematocyst nornenclature were used simultaneously. Besides the cnidae, aspects of their external anatomy and internal morphology were described; their systematic positions were also evaluated. The new species was included in the family Haliplanellidae due to the presence of three kinds of nematocysts in its acontia. It differs from H. lineata mainly in the presence of a sphincter in the former, absent in the latter. The diagnostic for the family was widened to accept the new genus within it.